KERUKUNAN HIDUP ANTAR UMAT BERAGAMA DAN IMPLIKASINYA PADA KETAHANAN WILAYAH (STUDI DI PADUKUHAN JATISARI, PLAYEN, GUNUNG KIDUL, DIY - Azan Pranoto (LPPM STISIP Persada Bunda, 2022)
This research focused on the harmony of interfaith religious life and its implications for regional resilience (A study in Jatisari, Playen, Gunungkidul, DIY). The purpose of this research are: to analyze the harmony of life among religious people and reviewing the implications in regional resilience. The research used descriptive qualitative method. The data collection technique is done by in-depth interviews and literature. Data analysis techniques used, namely: 1) data reduction, 2) data display, and 3) conclusion. The results showed that the harmony of life between religious in the semi-pseudo category is due to a limited and closed interpretation of harmony as a text that discusses facts and regulations (not meanings and values) that have developed so that it affects the resilience of the region which is still unstable, because dialogue between religious communities is not yet a discussion in which this will determine harmony until the practice of each individual to prevent potential conflicts, especially external factors, must be carefully reviewed